2022
DOI: 10.1111/petr.14451
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of SARS‐CoV‐2‐Positive donors in pediatric renal transplantation

Abstract: Background As COVID‐19‐positive donors are becoming more common, there is an increasing need for the transplant community to evaluate the safety and efficacy of organ transplant from a SARS‐CoV‐2‐infected donor. Methods Here we describe outcomes of two pediatric kidney transplant recipients who were vaccinated against COVID‐19 and received their allograft from a SARS‐CoV‐2‐positive donor. Results Both donors did not die from a COVID‐19‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…2,3 In the current issue of the Journal, two centers describe their experiences with using SARS-CoV-2 positive donors in non-lung pediatric solid organ transplantation (SOT). 4,5 These reports provide important insights on positive donors, only one lung transplant recipients developed COVID-19 potentially from a donor organ. 6 Although three cases of COVID-19 occurred in lung transplant recipients, two were thought to be due to secondary transmission events (one from a healthcare worker documented by whole genome sequencing, and one from a family member).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…2,3 In the current issue of the Journal, two centers describe their experiences with using SARS-CoV-2 positive donors in non-lung pediatric solid organ transplantation (SOT). 4,5 These reports provide important insights on positive donors, only one lung transplant recipients developed COVID-19 potentially from a donor organ. 6 Although three cases of COVID-19 occurred in lung transplant recipients, two were thought to be due to secondary transmission events (one from a healthcare worker documented by whole genome sequencing, and one from a family member).…”
mentioning
confidence: 98%
“…Pizzo et al reported successful short‐term outcomes in two pediatric kidney transplant recipients from asymptomatic SARS‐CoV‐2‐positive donors, with no recipients having developed COVID‐19 after SOT. 5 Both donors were found to have positive SARS‐CoV‐2 PCR by nasopharyngeal swab with high C t values (33.4 and 37.2 at 3 and 16 days prior to donation), and negative tracheal SARS‐CoV‐2 PCR, making remote infection more likely as the trend in C t value was increasing with time; further declines in viral load expected by the time of organ donation, which may in part explain the lack of transmission from SOT. Interestingly, the second donor in the report by Clark et al was managed using monoclonal antibodies (casirivimab/imdevimab) and remdesivir prior to organ recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation